Investigation of delays and connection stability in teleoperation via VR capabilities for remote exoskeleton-aided physiotherapy - Falkowski, Piotr; Zawalski, Krzysztof; Jeznach, Kajetan; Oleksiuk, Jan; Aktan, Mehmet Emin; Omurlu, Vasfi Emre; Niedbalski, Pawel; Akdogan, Erhan; Kolodziejski, Piotr (IEEE, 2025)
The research paper examines the challenges of remote control delays in exoskeleton-aided physiotherapy. It focuses on the implications of telerehabilitation requirements for safe treatment. As the global share of disabled and elderly people increases, the demand for effective teleoperated physiotherapy solutions rises, necessitating precise control over robotic systems. The study utilizes a mixed-methods approach to assess delays in communication between a rehabilitation exoskeleton and the control system's based on the digital twin in VR (virtual reality) components at different stages. Moreover, additional delays coming from distant operations are assessed. Key findings reveal that the average latency for joint control on shorter distances remains below 300 ms considered acceptable for comfortable manual teleoperation. The delays between setting the device's configuration and reaching it by a physical exoskeleton differ for particular joints and depend mainly on the torque-to-moment of inertia ratio. The total communication cycle should not exceed 400 ms, which can be further reduced by using a 6G network in the future or ADS (Automation Device Specification) communication protocol instead of the database. Ultimately, the study provides a foundation for developing algorithms that can mitigate delays and improve the efficacy of telehealth solutions with physically supportive devices.
Keywords: REHABILITATION; Engineering; Robotics